Analisis Kepuasan Pasien BPJS Kelas III Terhadap Pelayanan Rawat Inap Di RSU Haji Medan - Merry Moy Mita (Serat Acitya, 2022)
RSU Haji Medan is one of the hospitals in North Sumatra Province that is still experiencing problems with service quality. Health services for patients at RSU Haji Medan are still facing problems with limited consultation time with doctors, unsatisfactory drug services, inappropriate doctor visit schedules, uncomfortable wards, and nurses who are not friendly to patients. This research is a survey with a quantitative descriptive approach that aims to explain the effect of service quality on inpatient satisfaction at RSU Haji Medan. The population in this study were JKN inpatients at RSU Haji Medan, with a sample size of 50 people. Data were obtained through interviews using a questionnaire and analyzed using univariate and bivariate analysis. The results showed that the quality of service as measured through the aspects of physical evidence, responsiveness, reliability, assurance, and empathy affects the satisfaction of inpatients at RSU Haji Medan. It is suggested to RSU Haji Medan to improve the quality of service to patients by paying attention to the dimensions of service quality so as to increase patient satisfaction, The reliability dimension needs special attention because it is the most dominant aspect that influences patient satisfaction.